Assessment of Phytochemical Constituents, Antimicrobial Activity and Heavy Metal Contents of Gynura Procumbens (Dhaka University Journal of Pharmaceutical Sciences, 2024)
Abstract not availableDhaka Univ. J. Pharm. Sci. 23(2): 195-199, 2024 (December)